Hardware accelerator for anti-aliasing Wu's line algorithm using FPGA - Basma M. K. Younis; Ahmed Kh. Younis (Universitas Ahmad Dahlan, 2021)
Digital images are suffering from the stair-step effect because they are built from small pixels. This effect termes aliasing and the method uses to decrease so-called anti-aliasing. This paper offers a hardware accelerator of an anti-aliasing algorithm using HLS (high level synthesis) along straight-line segments or edges. These straight-line segments are smoothed by modifying the intensity of the pixel. The hardware implementation of two different architectures which is based on Zynq FPGA are presented in this work. The first architecture is built from one core while the second architecture is built from multi-core and uses a parallel technique to speed up the algorithm by dividing line segments into sub-segments and drawing them after smoothing instantaneously to formulate the main line. This parallel usage leads to a very fast execution of Wu's algorithm which is represented one-tenth hardware runtime for one core only. Also, the optimized resource utilization and power consumption for different cores have been compared, through single-core design which utilizes 8% and consumes 1.6 W, while utilized resources using 10 cores are 77% with a power consumption of 2 W.